Agricultural Resource Use and Management 2014
DOI: 10.1201/b17304-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Post-Harvest Organic Carbon Amendments as a Strategy to Minimize Nitrogen Losses in Cole Crop Production

Abstract: Abstract:Cole crops (Brassica vegetables) can pose a significant risk for N losses during the post-harvest period due to substantial amounts of readily mineralizable N in crop residues. Amending the soil with organic C has the potential to immobilize N and thereby reduce the risk for N losses. Four field trials were conducted to determine the effects of organic C amendments (OCA) on N dynamics and spring wheat (Triticum durum L.) harvest parameters proceeding early-and late-broccoli (Brassica olecerea var ital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 36 publications
(52 reference statements)
0
17
0
Order By: Relevance
“…However, cole crops can be harvested as late as November in temperate regions, which leaves little time for cover crop establishment. Both Nett et al (2011) and Congreves et al (2013b) found little evidence that cover crops reduced N losses after cauliflower or broccoli production, respectively. In order to overcome this limitation, Everaarts (1993) encouraged growers to undersow cover crops between the rows of a cole crop prior to harvest.…”
Section: Strategies To Minimize Post-harvest Nitrogen Lossmentioning
confidence: 93%
See 3 more Smart Citations
“…However, cole crops can be harvested as late as November in temperate regions, which leaves little time for cover crop establishment. Both Nett et al (2011) and Congreves et al (2013b) found little evidence that cover crops reduced N losses after cauliflower or broccoli production, respectively. In order to overcome this limitation, Everaarts (1993) encouraged growers to undersow cover crops between the rows of a cole crop prior to harvest.…”
Section: Strategies To Minimize Post-harvest Nitrogen Lossmentioning
confidence: 93%
“…Crop residue removal reduced SMN concentrations and potential N loss after broccoli harvest (Congreves et al 2013b), but most crop residue removal studies have focused on field crops, as reviewed by Agneessens et al (2014). Therefore more research is needed on the impact of crop residue removal in horticultural systems.…”
Section: Strategies To Minimize Post-harvest Nitrogen Lossmentioning
confidence: 98%
See 2 more Smart Citations
“…This means that when assessing the risk of post-harvest losses, the N content in the crop residues must be considered in addition to the potential for soil OM mineralization. Up to 198 kg·N·ha −1 may result from leaving broccoli crop residues in the field after harvest, representing a significant risk [69]. This situation may occur mainly for brassica crops, which are the ones with higher N contents (Table 1).…”
Section: Management Of Crop Residuesmentioning
confidence: 99%